Water policy and resilience of potable water infrastructure to climate risks in rural Malawi. (October 2022) - Joshua, Miriam Dalitso; Tompkins, Emma; Schreckenberg, Kate; Ngongondo, Cosmo; Gondwe, Esther; Chiotha, Sosten
Abstract: Adverse effects of climate risks on access to potable water are increasingly being acknowledged in sub Saharan Africa. Resilient infrastructure supported by appropriate governance arrangements, is therefore central to water security under these extreme weather events. For several decades, governments in sub Saharan Africa have developed governance arrangements including infrastructure and legislation to ensure water security. However, the effectiveness of policy consideration in resilience of potable water infrastructure to climate risks/extreme weather events as well as their seasonality has been a neglected area. Using Zomba rural in Southern Malawi as a case study, this study was therefore aimed at addressing this gap by assessing the effectiveness of local water policy responses to extreme weather events using the 2015 flooding effects on potable water in Zomba rural in Southern Malawi as a case study. The study firstly analysed rainfall and extremes indices for evidence of trends of climate risks in Zomba during the period from 1982 to 2015. To understand the effects of the 2015 flooding on water infrastructure and access to potable water as well as evaluate policy provisions for responses to climate risks, the study further applied a qualitative approach through policy document review, key informant interviews, focus group discussions. The results suggest a generally decreasing annual rainfall pattern with high variability by seasons and frequent occurrences of droughts and flooding. The annual rainfall decrease was not statistically significant at α = 0.05 level, whereas the extremes indices were statistically significant. However, the study found that current policy frameworks are more biased towards drought preparedness as compared to flooding preparedness. For instance, the 2015 floods destroyed vital water supply infrastructure and the responsible institutions could not rehabilitate the damaged infrastructure, leaving communities with intermittent and no supply of potable water for over six months. On the other hand, during dry seasons and drought conditions, the intakes are above the water level. These results show that the present rural water infrastructure is vulnerable and not resilient enough to extreme weather events. In addition, the water institutions are especially not prepared to handle flooding events and their impacts. In this regard, water legislation and infrastructure designs do not adequately take into consideration the effects of extreme events on access to potable water, making water security a challenge in rural Malawi. Highlights: Adverse effects of climate risks on access to potable water and infrastructure governance arrangement investigated. Extreme weather events of 2015 in Southern Malawi case study. Decreasing annual rainfall pattern with high variability by seasons and frequent occurrences of droughts and flooding. Water infrastructure not capable of coping with extremes. Current policy frameworks biased towards drought preparedness not flooding preparednes